RESEPSI MASYARAKAT TIMUR INDONESIA TENTANG “SOPI” (REINTERPRETASI TERHADAP EMPAT SERANGKAI AYAT KHAMAR) - Garwan, Muhammad Sakti (UIN Sunan Kalijaga Yogyakarta, 2020)
In this paper contains and describes how the people of Eastern Indonesia in the reception of verses about khamar, namely in an-Nahl (16): 67, QS. al-Baqarah (2): 219, QS. al-Maidah (5): 90, and QS. an-Nisa (4): 43. In the general view ofscholars khamar or the like, sopi is indeed something that is unlawful. This issue then raises problems in the lives of Eastern Indonesian people, who regard khamar or sopi as a symbol of brotherhood, encouragement of tradition and a turning wheel of the people's economy. This paper is qualitative in nature, combining library research and field research. The data in this paper were collected by observation techniques, and interviews were then analyzed using the analysis of the phenomenology of Edmund Husserl, with religious leaders, and traditional leaders as research subjects. This paper contains the formulation of the problem (1) How is the reception of Eastern Indonesian people about theverse khamar in the Qur’an? (2) What is the perception of the community in distinguishing mudharat and the benefits of drinks khamar? They show of community reception through four verses attention to three aspects, symbolizing brotherhood, tradition and players encouragement economy of the community, in the reception also showed a reinterpretation of the meaning of the verse of the Qur’an, in particular paragraph of the law to drink alcohol or gin, which in the science of usul fiqh can be categorized as a rukhshah, that is, a codification of law that is given shari'ah for the mukallaf who has difficulty in carrying out the taklif that is imposed on him.